Does Education Matter? The Value of Higher Education for Voice and Agency in Sweden - Annica Brännlund (Social Work & Society, 2014)
There is extensive research pointing to the positive effects of education in the form of labour market outcomes. These outcomes are vital when evaluating education; there are however additional outcomes of education that also might be important for good human life. From this point of view, education could affect non-market areas such as democracy, gender equality and civic engagement. This paper seeks to extend research through an analysis of the relation between level of education on two vital non-market capabilities: agency and voice. The study uses an eight-year longitudinal national survey of 1 058 Swedish youth, controlling for baseline values of voice and agency. Results show that university education increases young people's capabilities of voice and agency.